Papua New Guinea Rural Household Survey, 2023 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Papua New Guinea Rural Household Survey (2023) collected detailed household-level data on agricultural production, food and non-food consumption and expenditure, and livelihood strategies across 14 provinces, covering communities in the highlands, lowlands, and islands of Papua New Guinea (PNG). The survey was designed using a purposive sampling strategy based on defined agro-ecological zones, which allows for the analysis of key factors influencing rural households and communities. It is important to note that the survey is not nationally representative; however, given the careful random selection of survey areas, we expect that generalizable relationships between variables affecting socio-economic and other development outcomes in rural PNG communities will be consistently observed across representative samples and in this survey. These factors include those that contribute to more resilient local food systems, diversified employment opportunities, and improved household wellbeing. The survey encompasses 2,699 households in 270 communities, spanning five agroecological zones. It features detailed modules on a wide range of topics relevant to rural livelihoods, agricultural production, and household wellbeing.